Radio Komunitas : Membangun Era Baru dalam Demokratisasi Media Siaran - Ade Fadli Fachrul (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
Community radio is a form of public participation in carrying the democratic values ??in the realm of information, particularly information democracy, also known as the democratization of media. To achieve such ideals, however, media is controlled by the media capitalists are not allowed the other in the world of information. Here the role and function of community radio is required to play a strategy for achieving a democratic atmosphere of media. However broadly and heavy constraints are still lied, despite such beautiful dream is still opened. There is a hope in front of us towards a common goal to build alternative media.